Large eddy simulation of a turbulent flame using tabulated chemistry with a novel multivariate PDF. Issue 5 (28th May 2019) - Jesch, David; Bevrnja, Alija; di Mare, Francesca; Janicka, Johannes; Sadiki, Amsini
ABSTRACT: A novel, efficient method to account for multivariate probability density functions (PDFs) in the context of the flamelet generated manifolds (FGM) approach in a large eddy simulation (LES) framework is presented and discussed. It consists of applying the 'Correlation Set by Simulated Annealing (CSSA)' algorithm on univariate samples of each control variable to recombine them into multivariate samples in joint space, while accounting for the needed covariances. This is done on the fly and on a cell-by-cell basis. Thereby, the assumption of statistical independence of the control variables has been relaxed. The PDF is represented in a discrete manner and the integration is replaced through ensemble averaging. Consequently, the shape of the PDF no longer appears in the look-up table. The algorithm has been validated in the context of LES calculations of two configurations. Compared to a conventional pre-integrated FGM approach, the required CPU time has increased only modestly.